Design and experimental tests of a rotary active magnetic regenerator prototype. (October 2015) - Eriksen, D.; Engelbrecht, K.; Bahl, C.R.H.; Bjørk, R.; Nielsen, K.K.; Insinga, A.R.; Pryds, N.
Abstract: A rotary active magnetic regenerator (AMR) prototype with efficiency and compact design as focus points has been designed and built. The main objective is to demonstrate improved efficiency for rotary devices by reducing heat leaks from the environment and parasitic mechanical work losses while optimizing the utilization of the magnetized volume. Heat transfer calculations combined with 1D AMR modeling have revealed the necessity for an insulating air gap between magnet and regenerator when designing for high efficiency. 2D finite difference AMR modeling capturing the interplay between heat transfer fluid flow and an inhomogenous time-varying magnetic field in the individual regenerator beds has been used in the design process. For one operating point a COP of 3.1 at a temperature span of 10.2 K and a cooling power of 103 W were measured. Major issues limiting the performance have been identified and improvements are outlined for future work. Highlights: Rotary active magnetic regenerator prototype was designed, built and tested. Modeling reveals a benefit from an insulating air gap between regenerator and magnet. Modeling capturing flow/inhomogeneous magnetic field interplay was used for design. COP of 3.1 was achieved at a temperature span of 10.2 K and a cooling power of 103 W.